Design review of scissors lifts structure for commercial aircraft ground support equipment using finite element analysis - Rashid, Helmi; Mohd Ariffin, Mohd Khairol Anuar; Mohd Noh, Mohd Hafiz; Abdullah, Abdul Halim; Abdul Hamid, Ahmad Hussein; Mat Jusoh, Mohammad Azzeim; Othman, Akbar (Elsevier, 2012)

(untitled)
This research reviews scissors lifts structure manufactured by AEREX, UMW Advantech Sdn. Bhd. that is used on a catering hi-lift using Finite Element Analysis (FEA). The scissors lifts is one of the major and crucial components of a catering hi-lift which is mainly used to hoist the van body of the catering hi-lift for aircraft servicing. The catering hi-lift is one of the aircraft ground support equipment that is commonly used to service commercial airliners. For the design to be approved by the Department of Safety and Health (DOSH) Malaysia under Hoisting Machine Design according to DS-149 Standard,it must comply with specific engineering design standard. The only standard applicable is the ANSI Standard MH29.1-2003 “Safety Requirements for Industrial Scissors Lifts” (Revision on ANSI MH29.1-1994).Focusing on the deflection accordance to the ANSI Stan dard;calculation regarding the allowable maximum deflection must not be exceeded. To analyze, manual calculations, solid modeling and computer simulations were involved using state-of-the-art CAE software. Several linear static FEA analyses were done to get accurate results. The results show that the deflection is still in the acceptable range.However, some manufacturers find that the allowable maximum deflection is too excessive. Therefore, advice on critical areas to the application must be given and other safety precautions must be taken to avoid failure during operation.